Dynamic Marketing and Service Innovation for Service Excellence - Evo S. Hariandja; Togar M. Simatupang; Reza A. Nasution; Dwi Larso (Gadjah Mada International Journal of Business, 2014)
This study aims at creating a framework describing how the interaction capabilities between dynamic marketing and service innovation can influence service excellence. In this study market sensing, market learning, market targeting or positioning are classified as dynamic marketing capabilities (DMC), while sensing, seizing, and transformi ng are classified as service innovation capabilities (SIC). Hence, the drivers of service excellence for the framework being developed are divided into three main categories: dynamic marketing capability, service innovation capability, and their interaction. The findings of the study  on three hotels, ranging from 4-star to 5-star hotels and operating in Indonesia, suggest that both capabilities and their interaction play their roles in achieving service excellence.Abstrak: Riset ini bertujuan untuk menciptakan kerangka yang menggambarkan bagaimana kapabilitas interaksi antara pemasaran dinamik dan inovasi jasa dapat mempengaruhi keunggulan layanan. Dalam riset ini, penginderaan pasar, pembelajaran pasar, target pasar serta positioning diklasifikasikan sebagai kapabilitas pemasaran dinamik (DMC), sementara penginderaan (sensing), merebut (seizing), dan transforming diklasifikasikan sebagai kapabilitas inovasi jasa (SIC). Oleh karena itu, penggerak keunggulan layanan untuk kerangka yang dikembangkan dibagi menjadi tiga kategori utama: kapabilitas pemasaran dinamik, kapabilitas inovasi jasa, dan interaksi diantara kedua kapabilitas. Temuan studi pada tiga hotel yang dijadikan sebagai studi kasus di hotel bintang 4 (empat) dan 5 (lima) yang beroperasi di Indonesia, menunjukkan bahwa kedua kapabilitas dan interaksinya memainkan peran mereka dalam mencapai keunggulan layanan.